2022
DOI: 10.1177/19417381221101006
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow Restriction Therapy Preserves Lower Extremity Bone and Muscle Mass After ACL Reconstruction

Abstract: Background: Muscle atrophy is common after an injury to the knee and anterior cruciate ligament reconstruction (ACLR). Blood flow restriction therapy (BFR) combined with low-load resistance exercise may help mitigate muscle loss and improve the overall condition of the lower extremity (LE). Purpose: To determine whether BFR decreases the loss of LE lean mass (LM), bone mass, and bone mineral density (BMD) while improving function compared with standard rehabilitation after ACLR. Study Design: Randomized contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Our protocol replicated the personalized tourniquet systems, LOP, and repetition schemes that have demonstrated a positive effect in adults after ACLR. 23,26 These results provide further guidance to clinicians when making clinical decisions regarding the appropriate dosage and parameters of BFRT.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Our protocol replicated the personalized tourniquet systems, LOP, and repetition schemes that have demonstrated a positive effect in adults after ACLR. 23,26 These results provide further guidance to clinicians when making clinical decisions regarding the appropriate dosage and parameters of BFRT.…”
Section: Discussionmentioning
confidence: 78%
“…9,12,34,39 Recent clinical trials in adults after ACLR have shown positive effects of BFRT using consistent personalized tourniquet systems, limb occlusion pressure (LOP), and repetition schemes. 23,26 Although evidence is building in support of BFRT in the adult population, the effectiveness of BFRT in the adolescent population after ACLR has not yet been studied. The purpose of this study was to investigate the impact of BFRT on knee strength and function at 3 months postoperatively and at the time of return to sport (RTS).…”
mentioning
confidence: 99%
“…All patients in the RR group and RR + BFRT group received routine rehabilitation training from day 2 postoperatively, twice a week for 8 weeks. According to the literature ( Abe et al, 2006 ; Tegtbur et al, 2020 ; Jack et al, 2022 ) and our previous clinical experience, the routine rehabilitation training program was formulated: 1) 5 min warm-up exercise: including self-pulling and free walking-running on the elliptical machine; 2) Active ROM training of the lower extremity: sliding bed exercises for active knee flexion and extension, 10 repetitions per set, 10 s rest between sets, a total of 3 sets; 3) Squat training within the 0–90° motion arc: 10 repetitions per set, 10 s each time, 30 s rest between sets, a total of 3 sets; 4) Walking training for 5 min; 5) The German GYM80 intelligent strength training system was used to perform low-intensity pedaling closed-chain training within the range of motion of the knee joint from 0 to 90°. During muscle contraction, concentric and eccentric contractions alternate in rhythmic cycles of 1 s each.…”
Section: Methodsmentioning
confidence: 99%
“…BFRT was pioneered by SATO in Japan ( Abe et al, 2006 ), which enables compression of the limb through compression cuffs to reduce arterial inflow and block venous outflow during rehabilitation training ( Tegtbur et al, 2020 ). Jack et al (2022) compared the efficacy of BFRT with conventional rehabilitation in patients after anterior cruciate ligament reconstruction (ACLR). The results showed that patients after ACLR in BFRT group had comparable outcome measures of muscle strength and bone loss to those in conventional rehabilitation group at 12 weeks postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…BFR employs the use of an occlusion cuff to partially restrict arterial blood flow and completely restrict venous outflow to and from a distal muscle group [1][2][3] . When paired with light-weight exercise, BFR has demonstrated significant improvement in functional outcomes in humans experiencing muscle loss, including those recovering from orthopedic surgery [4][5][6][7][8] , aged populations 92, [10][11][12] , and those with metabolic disorders [13][14][15] . Although the positive clinical outcomes are promising, a better understanding of the underlying physiologic mechanisms would allow for development of improved therapeutic protocols for treating muscle loss.…”
Section: Introductionmentioning
confidence: 99%